2000
DOI: 10.1103/physrevlett.85.944
|View full text |Cite
|
Sign up to set email alerts
|

Modern Nuclear Force Predictions for theαParticle

Abstract: We present new calculations of the α-particle which are based on the most modern nucleon-nucleon interactions alone and combined with the Tucson-Melbourne or the Urbana IX three-nucleon interaction. Results for the binding energies and some properties of the wave function are given. On that phenomenological level little room is left for the action of a possible four-nucleon force.PACS numbers: 21.10.-h, 21.45.+v, 27.10.+h,21.30.-x Few nucleon bound states have received increasing attention in recent years. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
350
3
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(371 citation statements)
references
References 36 publications
16
350
3
2
Order By: Relevance
“…Exact benchmark calculations for the three-and four-body system [8,9,10,11,12] were very helpful in this respect. They also showed that three-body forces are needed, though different ones for different phase-shift equivalent two-body potentials.…”
Section: Off-shell Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exact benchmark calculations for the three-and four-body system [8,9,10,11,12] were very helpful in this respect. They also showed that three-body forces are needed, though different ones for different phase-shift equivalent two-body potentials.…”
Section: Off-shell Propertiesmentioning
confidence: 99%
“…Matrix elements of one-, two-, or three-body operators in A-body space can be calculated easily using an occupation number representation. Modern computers and numerical techniques can tackle A-body Hilbert spaces dimensions up to about 10 10 . These numbers are impressive but by far not sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a particular interaction coined as V low−k is shown to parameterize a high-order chiral effective field theory two-nucleon force. In the theory, a cutoff dependence can be used as a tool to assess the error in the truncation of nuclear forces to two-nucleon interactions and introduce low-momentum three-nucleon forces [71][72][73][74][75][76][77][78][79].…”
Section: B Gluons Quarks and Nucleonsmentioning
confidence: 99%
“…In order to avoid fake effects the relative thresholds in 4 He should be reproduced well, therefore we used also a 35-dimensional modelspace, called large,by allowing additional configurations with two orbital angular momenta on the two Jacoby coordinates yielding -6.69 MeV binding energy. This must be compared to −6.92MeV known from Faddeev calculations [18]. For the deuteron we use the structure given in [2], yielding a binding energy of -1.921 MeV, which could be easily improved.…”
Section: Rgm and Model Spacementioning
confidence: 99%